Truth and privilege : libel law in Massachusetts and Nova Scotia, 1820-1840 / Lyndsay Campbell, University of Calgary. - Campbell, Lyndsay (Studies in legal history., 2022)
Truth and Privilege is a comparative study that brings together legal, constitutional and social history to explore the common law's diverging paths in two kindred places committed to freedom of expression but separated by the American Revolution. Comparing Nova Scotia and Massachusetts, Lyndsay Campbell examines the development of libel law, the defences of truth and privilege, and the place of courts as fora for disputes. She contrasts courts' centrality in struggles over expression and the interpretation of individual rights in Massachusetts with concerns about defining protective boundaries for the press and individuals through institutional design in Nova Scotia. Campbell's rich analysis acts as a lens through which to understand the role of law in shaping societal change in the nineteenth century, shedding light on the essential question we still grapple with today: what should law's role be in regulating expression we perceive as harmful?